IRRIGATION DECISIONS AND USE OF GROUNDWATER IN BANGLADESH: PERSPECTIVES ON SOME EVOLVING CRISIS - Chowdhury, Afroza (American International Journal of Multidisciplinary Scientific Research, 2021)
Groundwater is one of the vital rechargeable natural capitals, which serves as the main water source around the globe. In Bangladesh, about 79% of the cultivated area relies on groundwater irrigation. The perspective piece is intended to scrutinize the irrigation decisions and groundwater use in Bangladesh from published sources. The paper points that the reason behind the excessive groundwater mining is imbedded in the heavy dependence of Bangladesh on irrigated dry season rice to feed its huge populaces. Bangladesh has obtained rice self-sufficiency by foregoing environmental costs. The farming communities as a whole rarely adopted water-saving modern technologies and keep paddy fields abundantly irrigated as the marginal cost of irrigation is near zero. The irrigation water price is commonly pre-negotiated on the basis of per unit area for the whole crop season without considering the volume of water. The perspective suggests that the ignorance about the importance of groundwater and the consequent over-extraction cannot be stopped without thorough policy reforms. Bangladesh should move toward institutionalizing irrigation, design a participatory framework involving all the stakeholders in a water management network and piloting efficient water models across the country.